Radical hysterectomy for stage IIB cervical cancer: A review - Prapaporn Suprasert (2018)
Patients with stage IIB cervical cancer in some countries in Europe and Asia especially in Japan are usually treated with radical hysterectomy and pelvic lymphadenectomy. Extrauterine diseases, ie, nodal metastases, parametrial invasion, and intraperitoneal spread, can be readily identified. We present the literature review of radical hysterectomy in stage IIB cervical cancer by searching data since 1980 from Medline, and we found that the parametrial involvement of patients in this stage was only 21-55%, the incidence of pelvic node metastases was about 35-45%, and 5-year survival rate was between 55% and 77%. Lymph node metastases and the number of positive nodes were significant prognostic factors of patients in this stage. © 2005 IGCS.